Review of Islamic Criminal Law on Sexual Relations Between Humans and Animals (Bestiality) in the KUHP: Tinjauan Hukum Pidana Islam Terhadap Hubungan Seksual antara Manusia dengan Hewan (Bestiality) dalam KUHP - Ibrahim, Faradhila Khusna; Rahma Eka Fitriani; Humaeroh, Nisbati Sandiah (Al-Jinayah : Jurnal Hukum Pidana Islam, 2025)
Bestiality is a type of crime related to crimes against decency, especially on the issue of sexual disorders, namely, having sexual intercourse with animals. This paper aims to answer questions about sexual harassment of animals according to Indonesian criminal law and how Islamic criminal law analyzes sexual harassment of animals in Indonesian criminal law. This type of research is qualitative and employs normative legal methods, focusing on the rules or norms that govern society. It is hoped that this research can increase public awareness about the dangers and negative impacts of bestiality. To enforce the law effectively, the Government needs to regulate and implement a more specific law on bestiality and provide relevant sanctions.